Intraocular pressure associations with refractive error and axial length in children. Issue 1 (23rd December 2003) - Lee, A J; Saw, S-M; Gazzard, G; Cheng, A; Tan, D T H
Abstract : Aim: To assess whether intraocular pressure (IOP) is associated with refractive error or axial length in children. Methods: Of subjects from the Singapore Cohort Study of the Risk Factors for Myopia (SCORM), 636 Chinese children aged 9–11 years from two elementary schools underwent non-contact tonometry, cycloplegic autorefraction, and A-scan biometry during 2001. For analyses, refractive error was categorised into four groups; hypermetropia (spherical equivalent refraction (SE) ⩾+1.0D), emmetropia (−0.5D<SE<+1.0D), low myopia (−3.0D<SE⩽−0.5D) and high myopia (SE⩽−3.0D). Results: Of the 636 children examined, 50.6% were male. The mean IOP was 16.6 (SD 2.7) mm Hg. There were no significant IOP differences between low (mean IOP = 16.4 (2.8) mm Hg) or high myopes (16.7 (2.5) mm Hg) and emmetropes (16.7 (2.9) mm Hg), p = 0.57. IOP was not correlated with spherical equivalent refraction (Spearman correlation, r = 0.009) or axial length ( r = 0.030). In regression analyses adjusting for diastolic blood pressure, neither spherical equivalent (regression coefficient = 0.014) nor axial length (regression coefficient = 0.027) were significantly associated with IOP. Conclusion: These findings do not support an association between IOP and refractive error or axial length in children. This questions postulated roles of IOP in the pathogenesis of myopia.